2013
DOI: 10.1128/aac.02612-12
|View full text |Cite
|
Sign up to set email alerts
|

Drug Combinations against Mucor irregularis In Vitro

Abstract: Combinations of terbinafine or caspofungin with amphotericin B, posaconazole, or itraconazole were studied as potential treatments against 18 isolates of Mucor irregularis in vitro. Synergism of the combinations of terbinafine with amphotericin B, posaconazole, and itraconazole against 38.9, 33.3, and 44.4% of the strains studied was observed. In contrast, synergism of the combinations of caspofungin with amphotericin B, posaconazole, and itraconazole against 99.4, 66.7, and 99.4% of the strains studied was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…In the combinations performed in this study, low MIC values were obtained and more than 80% of synergism against Cryptococcus was also observed, suggesting, that when combined, the drugs require lower concentrations to inhibit microorganisms. Similar studies have demonstrated a synergistic effect in vitro between azoles and TRB against Aspergillus , Cladophialophora carrioni, Fonsecaea pedrosoi, Phialophora verrucosa, Pythium , Scedosporium and Zygomycetes, using the chequerboard assay. Guerra et al .…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In the combinations performed in this study, low MIC values were obtained and more than 80% of synergism against Cryptococcus was also observed, suggesting, that when combined, the drugs require lower concentrations to inhibit microorganisms. Similar studies have demonstrated a synergistic effect in vitro between azoles and TRB against Aspergillus , Cladophialophora carrioni, Fonsecaea pedrosoi, Phialophora verrucosa, Pythium , Scedosporium and Zygomycetes, using the chequerboard assay. Guerra et al .…”
Section: Discussionsupporting
confidence: 54%
“…A possible explanation for the synergism between the antifungal agents in the combinations TRB + AMB and FCZ + TRB could be the fact that these drugs inhibit or disrupt the lipid ergosterol in the fungal membrane cell through different pathways or different enzymes . A study assessed the in vitro activity of TRB in association with VRZ, AMB and ITZ against clinical isolates of dematiaceous mould.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, and of major importance, the clinical significance of these and other in vitro and in vivo combination data remains uncertain [100].…”
Section: Genus and Species Identificationmentioning
confidence: 99%
“…Using Equation , the FICI was calculated for the cationic AMPs and their conjugated analogues against the MDR clinical pathogens using MIC values in Table . Because none of these analogues showed any activity against MDR K. pneumoniae (FADDI‐KP628) and P. aeruginosa (FADDI‐PA067) (Table ), their FICI were not calculated.…”
Section: Resultsmentioning
confidence: 99%
“…The synergistic activity of conjugated cationic AMPs with ÎČ‐lactam cephalosporin cores was then evaluated using FICI. This was calculated using the following formula, which was adapted from previous synergistic studies: FICI=FICAMPs+FICÎČ−lactam cephalosporin cores=true(MICconjugated AMPs/MICAMPstrue) + true(MICconjugated AMPs/MICÎČ−lactam cephalosporin corestrue) …”
Section: Methodsmentioning
confidence: 99%